2020
DOI: 10.1111/pbr.12874
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a putative orthologue of the wheat vernalization (VRN1) gene in perennial wheatgrass (Agropyron cristatum)

Abstract: Flowering time is important in the adaptation of crop plants to different environments and impacts the economic value of agricultural crops. Wheatgrass is a perennial Triticeae species and one of the most important grasses for pasture and forage in temperate regions of the world. Late heading is of interest in forage crop breeding programmes. Increasing the time to heading by molecular means may be facilitated by the identification and characterization of floral genes. In addition, the characterization of orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…By sequencing the transcriptome of a tetraploid A. cristatum accession, Zhou et al [53] found that the sequence similarity of most A. cristatum and wheat genes were greater than 95%. The synteny in homoeologous group 5 is also conserved between A. cristatum and wheat, as shown for agronomically important genes, such as the grain hardness (Ha) locus (mapped on the short arm of chromosome 5P) [54] and the vernalization (VRN-1) locus (mapped on the long arm of chromosome 5P) [55], indicating that these loci are collinear which those located on the short and long arms, respectively of chromosome 5 in each of the wheat A, B, and D genomes.…”
Section: Discussionmentioning
confidence: 94%
“…By sequencing the transcriptome of a tetraploid A. cristatum accession, Zhou et al [53] found that the sequence similarity of most A. cristatum and wheat genes were greater than 95%. The synteny in homoeologous group 5 is also conserved between A. cristatum and wheat, as shown for agronomically important genes, such as the grain hardness (Ha) locus (mapped on the short arm of chromosome 5P) [54] and the vernalization (VRN-1) locus (mapped on the long arm of chromosome 5P) [55], indicating that these loci are collinear which those located on the short and long arms, respectively of chromosome 5 in each of the wheat A, B, and D genomes.…”
Section: Discussionmentioning
confidence: 94%
“…Particularly for homologous groups 5 and 6, comparative mapping using a set of COS molecular markers showed that most of them were located on the short or long arms of wheat chromosome group 5 and 6 and were assigned to corresponding short or long arms of A. cristatum 5P and 6P chromosomes, respectively, indicating both homology between chromosomes 5P and 6P and wheat group 5 and 6, respectively [37]. In addition, synteny between A. cristatum and wheat homologous group 5 has also been demonstrated by mapping agronomically important genes, such as the grain hardness (Ha) and the vernalization (VRN-1) loci on the short and on the long arms of chromosome 5P, respectively [36,42], showing that these loci are collinear with those located on the short and the long arms, respectively, of chromosomes 5A, 5B and 5D in wheat. Together, these results indicated that a conservation of genes exists between wheat and A. cristatum chromosomes.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, these available wheat-A. cristatum addition lines allowed the location of molecular markers and genes for several important agronomic traits on specific A. cristatum chromosomes and chromosome arms [8,9,36,42]. However, no ditelosomic addition or substitution lines were previously obtained for the chromosome 5PS arm.…”
Section: Discussionmentioning
confidence: 99%